Four decades in the making: Collagen III and mechanisms of vascular Ehlers Danlos Syndrome - Ramla Omar (Elsevier, 2021)
Vascular Ehlers Danlos (vEDS) syndrome is a severe multi-systemic connective tissue disorder characterized by risk of dissection and rupture of the arteries, gastro-intestinal tract and gravid uterus. vEDS is caused by mutations in COL3A1, that encodes the alpha 1 chain of type III collagen, which is a major extracellular matrix component of the vasculature and hollow organs. The first causal mutations were identified in the 1980s but progress in our understanding of the pathomolecular mechanisms has been limited. Recently, the application of more refined animal models combined with global omics approaches has yielded important new insights both in terms of disease mechanisms and potential for therapeutic intervention. However, it is also becoming apparent that vEDS is a complex disorder in terms of its molecular disease mechanisms with a poorly understood allelic and mechanistic heterogeneity. In this brief review we will focus our attention on the disease mechanisms of COL3A1 mutations and vEDS, and recent progress in therapeutic approaches using animal models.